Analysis overheating problems of electric motor by type DK-409 and motor – driven compressor by type (EK – 7B) of continuous current locomotive by type (ER – 1, ER – 2) with using the thermal system of compensation - Krasnov, R. V. (Science and Transport Progress, 2011)
The article shows the method of investigation of thermal processes occurring in the electric compressor motor of rolling stock to determine the values of overheating, which will later be used to assess their impact on the state of isolation.